2020
DOI: 10.29173/iq976
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability through the liaison with data archive users

Abstract: As a social science data archive, we focus on collecting research data and archiving it. However, there are more responsibilities that come with data archiving: cooperation on international social surveys (ISSP, ESS), supporting secondary data analysis and much more. Significant part of our work is to communicate with students and researchers, to educate them about data management and data analysis. Although the relationship we have is functional and seems sufficient, we tend to ask ourselves: who are the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…They mainly use data that are easy to understand, and they mainly encounter challenges such as forming efficient search queries, understanding data, or opening and reading datasets. Two studies on the user profiles of social science data repositories showed a remarkably high prevalence of students: 28.6% of users of a Czech repository and 39% of users of a Finnish repository (Kudrnáčová and Trtíková 2020;Late and Kekalainen 2020).…”
Section: Four Key Challenges For Sharing Data In the Social Sciences ...mentioning
confidence: 99%
“…They mainly use data that are easy to understand, and they mainly encounter challenges such as forming efficient search queries, understanding data, or opening and reading datasets. Two studies on the user profiles of social science data repositories showed a remarkably high prevalence of students: 28.6% of users of a Czech repository and 39% of users of a Finnish repository (Kudrnáčová and Trtíková 2020;Late and Kekalainen 2020).…”
Section: Four Key Challenges For Sharing Data In the Social Sciences ...mentioning
confidence: 99%